(3QbGFb GdMbGFb aj MSGH GdOQL hGdObGFbs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s ((3eMeO Hf eUWai GdWfJGhi s)
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf hHYO ajbhd abjQ QMeI QHg djS ai MSGH GdGYeGd GdadcjI CMSf ef WQjb MSGH GdfSHI GdSJjfjI hgj GdeSJYedI ai YUQfG s
(3BNQgG (B:s
(3Ke RO GdNGQL Ydi GdOQLGJ GdUMjMGJ GdJi ef GdLOhd CfG cfJ CNPJ GdfGbU hGfbU Ef cfJ CNPJ GdRGFO jMUd GdeWdhH hGdBf bO ced dfG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B54 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B188s
Keywords: (3Gdadcs